2011
DOI: 10.1111/j.1551-2916.2011.04424.x
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering Kinetics of Pure α‐Alumina

Abstract: The microstructure development of sintered alumina at different stages in the spark plasma sintering process has been investigated. Based on classical kinetics laws and adapted Coble creep models of hot pressing, the densification and grain growth kinetics were analyzed as a function of various parameters such as heating rate, sintering temperature, and dwell duration. It is found that sintering kinetics are greatly influenced by heating rates. The local temperature gradients at interparticle contacts during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…For the samples sintered at the low heating rate closed porosity is initiated at 1050ºC (Figure 6a) and its relative contribution to the total porosity seems to increase with the sintering temperature but it is not detected at lower sintering temperatures (Figure 6b). This is in agreement with the findings that sintering kinetics is greatly influenced by heating rates [11].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For the samples sintered at the low heating rate closed porosity is initiated at 1050ºC (Figure 6a) and its relative contribution to the total porosity seems to increase with the sintering temperature but it is not detected at lower sintering temperatures (Figure 6b). This is in agreement with the findings that sintering kinetics is greatly influenced by heating rates [11].…”
Section: Resultssupporting
confidence: 82%
“…The powder was sintered using an SPS apparatus type HD P 25/1 (FCT Gmbh, Germany). Preparation details can be found elsewhere [11,12]. Mechanical pressure of 80 MPa was applied uniaxialy all over the heating and dwell step.…”
Section: Sample Preparation and Sps Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heating rate has been found to be a critical parameter in obtaining such a material. According to Aman et al [20], grainboundary diffusion probably dominates at low heating rates whereas grain coarsening, in respect of thermal equilibrium considerations, is unavoidable at high heating rates during the initial stages of low temperatures sintering. According to Kim et al [1], when sintering at under 1250 8C, rapid heating creates high defect concentrations inducing dynamic grain growth and thus decreasing the transparency of the material.…”
Section: Introductionmentioning
confidence: 99%
“…SPS is a processing technique that has been widely used over the past decades [1,5,[17][18][19][20]. It was shown that dense, finegrained materials can be developed at low temperatures and short sintering times compared to conventional techniques such as hot isostatic pressing (HIP).…”
Section: Introductionmentioning
confidence: 99%